Direct Contact Membrane Distillation for Separation of Hcl From A Mixture of Acids (Journal of Engineering, 2018)
HCl is separated from HCl –H2SO4  solution by membrane distillation process(MD). The flat –sheet membranes made from polyvinylidene fluoride (PVDF) and polypropylene (pp.). Plate and frame these types of membrane where used in the process. The feed is a mixture of HCl and H2SO4 acids compositions depended on metals treated object.HCl concentration increased in the permeate during the process but sulfuric acid increased gradually in the feed .During the concentration of solution acids concentrations in the feed at the beginning were 50 g/dm3 of sulfuric acid and 50 g/dm3 of hydrochloric acid at 333K feed temperature the permeate flux was 71 dm3/m2.d. At a higher  concentration of HCl  in the feed  111g /dm3  and 61 g/ dm3 of sulfuric acid  at the feed temperature 333K  volume permeate flux was 57 dm3/ m2.d . At a higher concentration of  sulfuric acid  in the feed 161 g/dm3 and 60 g/dm3 of HCl decrease the permeate flux from 71 to 35 dm3/m2.d at 333K . The permeate flux increase from 35 at 333K to 85 at 343 K increase the temperature caused an increase in permeate flux. Increases in sulfuric acid concentration from 50 to 161 g/dm3 decrease the volume permeate flux from 71 to 35 dm3 /m2.d, HCl concentration was achieved a higher value 9.1 g/dm3 during the process at the feed concentration 161g/dm3 of sulfuric acid and 60g/dm3 of hydrochloric acid at feed temperature 343K.